The usefulness of infra-annual government cash budgetary data for fiscal forecasting in the euro area - Luca Onorante; Diego J. Pedregal; Javier J. Pérez; Sara Signorini (European Central Bank (ECB), 2008)
Short-term fiscal indicators based on public accounts data are often used by European policy makers. They represent one of the main sources of publicly available intra-annual fiscal information. Nevertheless, these indicators have received limited attention from the academic literature analysing fiscal forecasting in Europe. Some recent literature suggests the validity of public accounts data to forecast government deficits in the euro area. We extend this literature on two fronts:(i) we shift the focus from indicators of government deficits to look at indicators for government total revenue and total expenditure; (ii) we use a mixed-frequency state-space model to integrate readily available monthly/quarterly cash-based fiscal data with annual general government series (National Accounts). By doing so, we are able to maintain the focus on forecasting and monitoring annual outcomes, while making use of infra-annual fiscal information, available within the current year. The paper makes a case for the use of monthly cash indicators for multi- lateral fiscal surveillance at the European level.
Keywords: C53; E6; H6; 330; euro area; Fiscal forecasting and monitoring; leading indicators; Öffentlicher Haushalt; Wirtschaftsindikator; Frühindikator; Haushaltsdefizit; Eurozone; Theorie; EU-Staaten